The validity and reliability of the Turkish version of the "parental satisfaction with caregiving for children with developmental disabilities" scale (Annals of Medical Research, 2021)
Aim: Parents of children with special needs face many difficulties. Additional support may be required for parents who are not satisfied with their disabled child's care. This study aimed to develop the Turkish validity and reliability study of "parental satisfaction with caregiving for children with developmental disabilities", which is evaluated the satisfaction of the parent who gives the care child with a special need. Materials and Methods: This study included one hundred forty-seven parents, who gave care of children with intellectual disability and autism spectrum disorder. Detailed information gave to participants and their informed consent was obtained. Student t, Mann-Whitney U, Anova and Kruskal Wallis tests were used for statistical evaluation.Results: The coefficient of Cronbach Alpha was 0.848 and that had a high degree of reliability. The coefficient of Cronbach Alpha of the satisfaction with the child was 0.812 and personal satisfaction was 0.784. In the analysis, KMO value was 0.795; Bartlett's value was also determined as 580.692, which was found statistically significant (p 0.00).Conclusion: This scale is expected to help researchers identify factors associated with parents' satisfaction with care and also identify factors that make the care process a positive experience for parents. Clinicians and caregivers can use this scale to determine whether parents with children with behavioral problems need additional support.
Keywords: Caring parent; children with special needs; parental satisfaction